Tele-Physiotherapy for Older Adults: A Scoping Review of Feasibility, Accessibility, and Clinical Outcomes - Catherine Hermawan Salim; Astrid Komala Dewi; Linauli Happy Christina Zega (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid expansion of digital health technologies has increased interest in tele-physiotherapy as an alternative or complementary approach to traditional in-person rehabilitation for older adults. However, evidence regarding its feasibility, accessibility, and clinical outcomes remains fragmented across different populations and delivery models. This scoping review aimed to explore and synthesize current evidence on the feasibility, accessibility, and clinical effectiveness of tele-physiotherapy interventions for older adults published between 2020 and 2025. A systematic search was conducted across four major databases, PubMed, Scopus, and Google Scholar, for studies published from 2020 to 2025. Inclusion criteria comprised peer-reviewed articles involving older adults (≥60 years) who received physiotherapy via telehealth platforms. Studies focusing on feasibility, usability, or clinical outcomes were included. After screening 490 articles and removing duplicates, 8 studies met the inclusion criteria. Data were extracted on study design, sample characteristics, interventions, and outcomes. Tele-physiotherapy represents a promising, cost-effective, and accessible rehabilitation strategy for older adults, particularly in contexts with restricted physical access to healthcare. Although feasibility and short-term effectiveness are well-supported, further research is required to evaluate long-term outcomes. Integrating tele-physiotherapy into geriatric care models could enhance continuity of care and promote functional independence in the aging population.